Studi Eksploratori tentang Pemahaman dan Implikasi Umpan Balik dalam Pembuatan IDP pada Pegawai PT PLN (Persero) - Febriana Sariati Marpaung (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
The aim of this study was to explore the impact of strength-based feedback provided by two different agents (assessor and direct supervisor) to improve employee’s competencies through the implementation of an Individual Development Plan (IDP). Data were collected sequentially with quantitative methods where participants filled out an IDP comprehension questionnaire and qualitative method by conducting semi-structured interviews with selected participants to deepen their understanding regarding the given feedback and IDP. Total participants were 39 employees. The results showed there was no significant difference regarding participants' understanding of their assessment results from the two different feedback agents. Although there were some differences in the experience of participants in the process of receiving feedback, in general, participants understand about the development that will be planned through IDP. In order to optimize the impact of feedback, several things are necessary to be considered i.e. feedback need to be delivered in personal situation and aligned with concrete behaviors at work, and it is important to monitor and evaluate the progress achieved by the employee.